KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL DALAM MELAKUKAN PENYIDIKAN TERHADAP TINDAK PIDANA PENCUCIAN UANG YANG BERSUMBER DARI TINDAK PIDANA ASAL - Hendra, Hendra (Faculty of Law, University of Palembang, 2021)
The crime of money laundering is a crime that is included in organized crime and therefore efforts to overcome it must use strong legal instruments. There are six institutions that have the authority to investigate money laundering cases. The six institutions are the Indonesian National Police, the Attorney General's Office, the Corruption Eradication Commission (CEC), the National Narcotics Agency (NNA), the Directorate General of Taxes and the Directorate of Customs and Excise and the Ministry of Finance. In addition to the six institutions regulated in the law above, there are still institutions that have the authority to investigate money laundering crimes that investigate cases of predicate offence, namely civil servant investigators. Therefore, the focus of the problem is what is the position of Civil Servant Investigators (CSI) in the Justice System in Indonesia and how is the authority of Civil Servant Investigators (CSI) in conducting investigations of money laundering crimes originating from predicate crimes. The research method used is a normative legal research method by taking a statutory approach and a case approach. Conclusions are drawn using deductive logic. The results of the study show that based on the Criminal Procedure Code and other laws and regulations, Civil Servant Investigators in the criminal justice system in Indonesia are authorized to carry out investigations according to the law which is the legal basis, and in carrying out their duties are under the coordination and supervision of Polri investigators. The authority of PPNS to investigate money laundering crimes originating from predicate crimes is in accordance with the laws and regulations and the decision of the constitutional court number 15/PUU-XIX/2021 whose decisions are final and binding. Therefore, all Civil Servant Investigators who have investigated predicate crimes given by law are authorized to investigate money laundering crimes.